EDUKASI KESEHATAN TENTANG DIABETES MELITUS PADA MASYARAKAT DI KELURAHAN SASA - Nabiu, Siti Amina Mia P; Muhammad, Fitra Tunisyah; Subah, Grestiyana; Lestari, Tutik (MAJU : Indonesian Journal of Community Empowerment, 2025)
Diabetes mellitus is a chronic disease whose prevalence is increasing in Indonesia. The level of community knowledge and behavior in preventing diabetes mellitus greatly determines the success of promotive and preventive efforts. This activity aims to improve knowledge and behavior in preventing diabetes mellitus. Community service is carried out through interactive counseling in Sasa Village, especially RT 12, using pre-test and post-test methods. There were 15 participants, dominated by the 15–24 year age group. Educational materials include symptoms, risk factors, and steps to prevent diabetes mellitus. The pre-test results showed that the majority of participants had a low level of knowledge. After the counseling, there was a significant increase. The post-test results showed that the education provided was effective in increasing participants' understanding of diabetes mellitus. Health education has been proven effective in increasing public knowledge about diabetes mellitus and can be an important strategy in efforts to prevent this non-communicable disease.